The contribution of the Monetary Studies Programme to Caribbean econometric modelling - Watson, Patrick ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1998)
Examines a sample of the contributions to the RPMS/CCMS conferences having an econometric content. Evaluates the soundness of the econometric practice at the time; the conclusions drawn and suggested policy prescriptions; the contribution to the understanding of the Caribbean economic reality; and, the contributions to Caribbean econometric practice.